COVID‐19 hospital and emergency department visitor policies in the United States: Impact on persons with cognitive or physical impairment or receiving end‐of‐life care. Issue 1 (20th January 2022) - Lo, Alexander X.; Wedel, Logan K.; Liu, Shan W.; Wongtangman, Thiti; Thatphet, Phraewa; Santangelo, Ilianna; Chary, Anita N.; Biddinger, Paul D.; Grudzen, Corita R.; Kennedy, Maura
Abstract: Objective: To characterize the national distribution of COVID‐19 hospital and emergency department visitor restriction policies across the United States, focusing on patients with cognitive or physical impairment or receiving end‐of‐life care. Methods: Cross‐sectional study of visitor policies and exceptions, using a nationally representative random sample of EDs and hospitals during the first wave of the COVID‐19 pandemic, by trained study investigators using standardized instrument. Results: Of the 352 hospitals studied, 326 (93%) had a COVID‐19 hospital‐wide visitor restriction policy and 164 (47%) also had an ED‐specific policy. Hospital‐wide policies were more prevalent at academic than non‐academic (96% vs 90%; P  < 0.05) and at urban than rural sites (95% vs 84%; P  < 0.001); however, the prevalence of ED‐specific policies did not significantly differ across these site characteristics. Geographic region was not associated with the prevalence of any visitor policies. Among all study sites, only 58% of hospitals reported exceptions for patients receiving end‐of‐life care, 39% for persons with cognitive impairment, and 33% for persons with physical impairment, and only 12% provided policies in non‐English languages. Sites with ED‐specific policies reported even fewer exceptions for patients with cognitive impairment (29%), with physical impairments (24%), or receiving end‐of‐life care (26%). Conclusion: Although the benefits of visitor policies towards curbing COVID‐19 transmission had not been firmly established, such policies were widespread among US hospitals. Exceptions that permitted family or other caregivers for patients with cognitive or physical impairments or receiving end‐of‐life care were predominantly lacking, as were policies in non‐English languages.